OMEGA-3 POLYUNSATURATED FATTY ACIDS IN THE TREATMENT OF PATIENTS WITH CARDIOVASCULAR DISEASES - A. V. Govorin; A. P. Filev (Столичная издательская компания, 2015)
For today there are convincing evidences of beneficial effect of ω-3 polyunsaturated fatty acids (PUFA) - eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids - in a number of cardiovascular diseases. Efficacy of ω-3 PUFA was confirmed by results of the large-scale clinical trials. Data on ω-3 PUFA efficacy in heart failure and cardiac arrhythmia were received, besides their well-known hypolipidemic effect. Low level of ω-3 PUFA biomarker , ω-3 index (content of EPA and DHA in erythrocytes), is considered as a risk factor of coronary heart disease as well as a risk factor of fatal arrhythmias. Use of standardized medicinal product with high content of EPA and DHA leads to the positive therapeutic effect in patients with different cardiovascular diseases.